Functional characterization of the Frost gene in Drosophila melanogaster: importance for recovery from chill coma. - Colinet, H.; Lee, S.F.; Hoffmann, A. (PLoS ONE, 2010)
Almost all animals, including insects, need to adapt to temperature fluctuations. The molecular basis of thermal adaptation is not well understood, although a number of candidate genes have been proposed. However, a functional link between candidate genes and thermal tolerance has rarely been established. The gene Frost (Fst) was first discovered when Drosophila flies were exposed to cold stress, but the biological function(s) of Fst has so far not been characterized. Because Fst is up-regulated after a cold stress, we tested whether it was essential for chill-coma recovery.A marked increase in Fst expression was detected (by RT-PCR) during recovery from cold stress, peaking at 42-fold after 2 h. The GAL4/UAS system was used to knock down expression of Fst and recovery ability was assessed in transgenic adults following 12 h of chill coma at 0 degrees C. The ability to recover from cold stress (short-, medium- and long-term) was significantly altered in the transgenic adults that had Fst silenced. These findings show that Fst plays an essential role in the recovery from chill coma in both males and females.The Frost gene is essential for cold tolerance in Drosophila melanogaster and may play an important role in thermal adaptation.